Organizational structure and basic functions of international convention «SportAссord» activity - Долбишева Ніна Григорівна (Nina Dolbysheva) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define and determine the basic functions of International convention “SportAссord” activity within the framework of international sport movement. Materials and methods: 21 literary sources have been analyzed. Results: International convention “SportAссord” is a nongovernmental sport organization, which unites, supports, coordinates and protects international sport federations and organizations in the international sport movement. “SportAссord” does its activities in accordance with United Nations General Assembly Resolution 1296 (XLIV), provisions of the International Olympic Charter and Code of Ethics, grounding on World Anti-Doping Code. The president is the head of administrative office, with the departments and board of executive body under control. General Assembly is the supreme authority, which carries out the range of basic tasks and grants authority to the management of “SportAccord” and its members for them to fulfill general and special functions. Conclusions: the International convention “SportAccord” activity is aimed at carrying out tasks by fulfilling general and special functions on the basis of international and internal legal documents.